The Effect of Blended Learning Approaches in Faculty Development Programs - Fatemeh Keshmiri (Strides in Development of Medical Education, 2022)
Background: The necessity of responding to changes and promoting the quality of education has increased the necessity of applying new approaches to empowerment programs.Objectives: The present research aimed to determine the effects of mid-term empowerment programs using a blended approach in the form of flipped classrooms (asynchronous, live meetings) before the coronavirus disease 2019 (COVID-19) epidemic and a virtual (asynchronous-synchronous) approach during the COVID-19 epidemic on teachers’ learning and satisfaction concerning teacher roles in the medical science education system.Methods: This study was quasi-experimental, and its participants were faculty members of Shahid Sadoughi University of Medical Sciences, participating in the empowerment program. This program was implemented in four periods, including 20 training sessions concerning the roles of a teacher in educational systems in the areas of “professional commitment, lesson planning, teaching-learning methods, assessment and evaluation methods, production of educational products, effective communication, and classroom management”. The program evaluation was performed using the participants’ levels of learning and satisfaction by scenario-based questions and a questionnaire, respectively. The results of different blended education approaches were compared in two time periods, before and during the COVID-19 epidemic. Data were analyzed using descriptive (mean and standard deviation) and inferential (independent T-test) tests. P >0.05 was considered the significance level.Results: One hundred and eighteen faculty members participated in the study, of whom 56 were female (47.5%), and 62 were male (52.5%). The faculty members’ satisfaction scores with blended empowerment courses with the flipped classroom were reported as 4.34±0.16 and the virtual blended classroom as 3.26±0.59. A significant difference was observed between satisfaction scores in different periods (P=0.001). The participants’ learning scores in the programs held by the blended approach with the flipped classroom (82.16±32.20) were significantly higher than those held during the COVID-19 epidemic (virtual approach) (59.23±48.53).Conclusion: The satisfaction and learning of participants in the flipped classroom program and the virtual blended classroom were at favorable and average levels, respectively. This difference in learning and satisfaction from the perspective of faculty members was significant. Therefore, interactive approaches in different virtual education platforms and a blended approach in empowerment programs are recommended.